2011
DOI: 10.1177/1359105310392416
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic variations in the caregiver role: A qualitative study

Abstract: The present study aimed to establish an in-depth qualitative analysis of the convergence and divergence of the experiences of caregivers from four ethnic groups. Eight Bangladeshi, nine Indian, four Pakistani and nine White-British caregivers participated in five focus groups. Differences and similarities between motivations for role adoption, willingness to care, experience of role, adaptation to role, coping, use of and satisfaction with support were discussed. Key differences were found in adaptation to car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 16 publications
6
64
0
5
Order By: Relevance
“…Esses resultados estão em consonância com outro estudo, em que todos os cuidadores afirmaram que não tinham escolha, a não ser adotar o papel de cuidador, pois não havia outra pessoa para desempenhar essa função. 5 A ausência de opção para cuidar da pessoa idosa confere destaque ao dever e à obrigação, entre os motivos que levam as idosas a cuidarem do idoso em domicílio. Apesar do cuidado não ter se constituído a primeira opção, algumas idosas demonstram estarem dispostas a continuar cuidando.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Esses resultados estão em consonância com outro estudo, em que todos os cuidadores afirmaram que não tinham escolha, a não ser adotar o papel de cuidador, pois não havia outra pessoa para desempenhar essa função. 5 A ausência de opção para cuidar da pessoa idosa confere destaque ao dever e à obrigação, entre os motivos que levam as idosas a cuidarem do idoso em domicílio. Apesar do cuidado não ter se constituído a primeira opção, algumas idosas demonstram estarem dispostas a continuar cuidando.…”
Section: Discussionunclassified
“…16 Cuidadores afirmam que a motivação para adotar esse papel se deu a partir de sua natureza bondosa, laços emocionais e por causa dos votos de casamento. 5 O elo familiar promovido pelo casamento também motivou as idosas da pesquisa a cuidar da familiar em domicílio. Percebe-se que algumas colaboradoras associaram a responsabilidade de cuidar do outro à obrigação matrimonial.…”
Section: Consider Ações Finaisunclassified
See 1 more Smart Citation
“…In addition, cultural norms of duty and filial obligations related to ethnicity and caring may result in disagreement between carer and care‐recipient on needs for services (Pinquart & Sörensen , Ahmed & Rees Jones , Williams & Johnson , Parveen et al . ). Disagreement between daughter‐carers and care‐recipient parents has been found in international studies on perceived unmet need for services, with the daughter‐carer perceiving more unmet need than their parent (Zweibel & Lydens , Van der Roest et al .…”
Section: Introductionmentioning
confidence: 97%
“…These findings support those of family caregiver studies which reported (1) stress emanating from the burden of additional responsibilities attendant to caregiving (Bessa et al, 2012;Streid et al, 2014) and (2) interpersonal stress in homes as women re-organized their schedules so as to prioritize caring for family members with cancer, which meant less time for spouses and children (Wells et al, 2008). Findings also depict caregiving among women in Nairobi as being motivated by a sense of loyalty to family, as reflected in various published studies in Africa (Aga et al, 2009;Tarimo et al, 2009;Yusuf et al, 2011) and elsewhere (Doumit et al, 2008;Parveen et al, 2011;Wells et al, 2008).…”
Section: Discussionmentioning
confidence: 96%